A high‐throughput UHPLC–MS/MS method for the quantification of five aged butyrylcholinesterase biomarkers from human exposure to organophosphorus nerve agents. (9th October 2016) - Graham, Leigh Ann; Johnson, Darryl; Carter, Melissa D.; Stout, Emily G.; Erol, Huseyin A.; Isenberg, Samantha L.; Mathews, Thomas P.; Thomas, Jerry D.; Johnson, Rudolph C.
Abstract: Organophosphorus nerve agents (OPNAs) are toxic compounds that are classified as prohibited Schedule 1 chemical weapons. In the body, OPNAs bind to butyrylcholinesterase (BChE) to form nerve agent adducts (OPNA–BChE). OPNA–BChE adducts can provide a reliable, long‐term protein biomarker for assessing human exposure. A major challenge facing OPNA–BChE detection is hydrolysis (aging), which can continue to occur after a clinical specimen has been collected. During aging, the o ‐alkyl phosphoester bond hydrolyzes, and the specific identity of the nerve agent is lost. To better identify OPNA exposure events, a high‐throughput method for the detection of five aged OPNA–BChE adducts was developed. This is the first diagnostic panel to allow for the simultaneous quantification of any Chemical Weapons Convention Schedule 1 OPNA by measuring the aged adducts methyl phosphonate, ethyl phosphonate, propyl phosphonate, ethyl phosphoryl, phosphoryl and unadducted BChE. The calibration range for all analytes is 2.00–250. ng/mL, which is consistent with similar methodologies used to detect unaged OPNA–BChE adducts. Each analytical run is 3 min, making the time to first unknown results, including calibration curve and quality controls, less than 1 h. Analysis of commercially purchased individual serum samples demonstrated no potential interferences with detection of aged OPNA–BChE adducts, and quantitative measurements of endogenous levels of BChE were similar to those previously reported in other OPNA–BChE adduct assays.